2013
DOI: 10.1289/ehp.1306761
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Cancer and Traffic-Related Air Pollution Exposure in Pregnancy and Early Life

Abstract: Background: The literature on traffic-related air pollution and childhood cancers is inconclusive, and little is known on rarer cancer types.Objectives: We sought to examine associations between childhood cancers and traffic-related pollution exposure.Methods: The present study included children < 6 years of age identified in the California Cancer Registry (born 1998–2007) who could be linked to a California birth certificate (n = 3,590). Controls were selected at random from California birthrolls (n = 80,224)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
77
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(86 citation statements)
references
References 70 publications
5
77
1
1
Order By: Relevance
“…Consistent with our findings, previous studies looking at CNS tumours found no [29][30][31] or only weak evidence [28] of an increased risk associated with proximity to highly trafficked roads. To our knowledge, only three other studies have investigated lymphoma in relation to traffic exposure [11,28,29]. Consistent with our study, they found no evidence of an association.…”
Section: Main Findingssupporting
confidence: 90%
See 3 more Smart Citations
“…Consistent with our findings, previous studies looking at CNS tumours found no [29][30][31] or only weak evidence [28] of an increased risk associated with proximity to highly trafficked roads. To our knowledge, only three other studies have investigated lymphoma in relation to traffic exposure [11,28,29]. Consistent with our study, they found no evidence of an association.…”
Section: Main Findingssupporting
confidence: 90%
“…Due to the small number of AML cases in our study, we did not perform separate analyses for AML. Another recent case-control study from California using modelled carbon monoxide as a proxy for traffic related pollution showed a positive association for ALL but not for CNS tumours [11]. A Danish case-control study found an increased risk with higher levels of modelled nitrogen monoxide and benzene for Hodgkin's lymphoma, but not for leukaemia or CNS tumours [29].…”
Section: Main Findingsmentioning
confidence: 98%
See 2 more Smart Citations
“…Heck et al examined associations between childhood cancers and traffic-related exposures to PM 2.5 and CO, both in utero, and during the child's first year. The CALINE model, traffic density metrics, and monitor measurements were all used as exposure metrics, with weak associations found between exposure metrics and several childhood cancers (Heck et al 2013).…”
Section: Studies Of Chronic Health Effects Associated With Long-term mentioning
confidence: 99%